Studi Morfometrik dan Meristik Ikan Jebung (Abalistes stellaris) di PPN Sungailiat Kabupaten Bangka - Sebayang, Monischa Br; Yuspita, Ni Luh Eta; Ratnapuri, Valentin Vina; Yandi, Misri; Maulana, Ali Rizki; Hasyimi, Wahid; Ainin, Dewi Tumatul (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study was conducted at PPN Sungailiat, Bangka Regency, to identify morphometric and meristic characteristics of Jebung fish (Abalistes stellaris), as well as environmentally friendly fishing gear. The research method used was descriptive with a simple random sampling technique to collect fish samples. Data were collected through observation and interviews, then analyzed using morphometric and meristic identification. The results showed that Jebung fish had 23 morphometric characters and 9 meristic characters, with an average total length of 30.5 cm and a standard length of 27 cm. Fin characteristics showed significant differences compared to other fish in the same family. In addition, the recommended fishing methods are bubu and bottom fishing to maintain the sustainability of the fish population. The conclusion of this study is that Jebung fish has distinctive morphometric and meristic characteristics, and requires an ecosystem-based management strategy to maintain its sustainability. The results of this study can serve as a basis for better fisheries resource management policies in the Bangka region.